Optogenetic Interrogation of Circuits Following Neurotrauma - Ceto, Steven; Courtine, Grégoire (Frontiers in Molecular Neuroscience, 2021)
Biological and engineering strategies for neural repair and recovery from neurotrauma continue to emerge at a rapid pace. Until recently, studies of the impact of neurotrauma and repair strategies on the reorganization of the central nervous system have focused on broadly defined circuits and pathways. Optogenetic modulation and recording methods now enable the interrogation of precisely defined neuronal populations in the brain and spinal cord, allowing unprecedented precision in electrophysiological and behavioral experiments. This mini-review summarizes the spectrum of light-based tools that are currently available to probe the properties and functions of well-defined neuronal subpopulations in the context of neurotrauma. In particular, we highlight the challenges to implement these tools in damaged and reorganizing tissues, and we discuss best practices to overcome these obstacles.